Implementation of Education and Education Manpower Recruitment Patterns In SD IT Al-Ihsan Baleendah Bandung - Muslihah, Neni Nadiroti; Nurseha, Alamsyah; Mutaqin, Ejen Jenal; Asy’ari, Lutfi (Universitas Sebelas Maret, 2021)
Educators and education personnel are one of the most important elements in improving the quality of education. Human resources are important in achieving the goals of an institution or organization, because HR is the driving force of other resources. Competition between Integrated Islamic Primary Schools in Bandung Regency, especially in Baleendah District will have an impact on the quality of recruitment of Educators and Education Personnel, as has been done by SDIT Al-Ihsan Baleendah. The focus of this study is the analysis of the recruitment of teaching staff and education personnel at SDIT Al-Ihsan Baleendah. This study aims to capture the recruitment strategy carried out by SDIT Al-Ihsan Baleendah. This type of research is a qualitative descriptive study. In the data collection technique, various techniques were used in this study, namely interviews, observation and documentation. The data analysis procedure used in this study was qualitative analysis. Based on the findings from the research results, it was concluded that the implementation of recruitment at SDIT Al-Ihsan Baleendah was carried out through administrative tests, interviews and practice stages.